Unsur Kelumit Esensial (Mn Dan Zn) dalam Biji Kakao (Theobroma Cacao L.) dari Daerah Perkebunan Ransiki Papua Barat - Sabir Sumarna; Yunita Pare Rombe; Murtihapsari Murtihapsari; Apriani Sulu Parubak; Christiana Niken Larasati; Putri Sarera Surbakti; Arniana Anwar (Jambura Journal of Chemistry, 2022)
Cocoa is a rich source of essential minerals and contributes a significant amount of minerals in the human diet. Processed products from cocoa in the form of chocolate are in great demand by almost everyone from various statuses and social groups. The high consumption of chocolate is also not a fact that chocolate is beneficial to human health. The essential minerals (Mn and Zn) in cocoa beans are needed by the human body as a source of minerals, but if excess can be harmful to the body. The purpose of this study was to determine the content of essential trace elements in cocoa beans and their potential as raw materials for food products. The analysis method uses AAS (Atomic Absorption Spectrophotometry). The results showed the content of micronutrients (Mn and Zn) in cocoa beans at five location points with an average value of 0.8976 mg/100 g and 5.7534 mg/100 g.